Comprehensive approach to choosing surgical tactics for locally advanced forms of colorectal cancer in patients of older age groups - N. A. Maistrenko; V. S. Chirsky; A. A. Sazonov; A. A. Erokhina (Вестник хирургии имени И.И. Грекова, 2019)
The objective is to improve the results of treatment of locally advanced colorectal cancer in patients of older age groups due to the personalized approach to choosing surgical tactics with a comprehensive assessment of the functional operability and molecular biological properties of the tumor.Material and methods. A comparative evaluation of the results of surgical treatment of locally advanced colorectal cancer in patients of different age groups was conducted on representative clinical material. We studied the molecular profile of tumors, taking into account the age factor, and the clinical significance of specific markers in predicting the results of treatment.Results. The most significant indicators of functional operability of patients that must be considered when choosing a surgical tactic were identified. . The features of the immunophenotype of tumors, taking into account the age factor, were determined; and the prognostic significance of specific immunohistochemical indicators was estimated.Conclusion. The use of a personalized approach to choosing surgical tactics allows to achieve encouraging results of treatment in geriatric patients with locally advanced colorectal cancer.